BUILDING POST-DISASTER HOUSEHOLD ECONOMIC RESILIENCE: OPTIMIZING ZAKAT FOR MICROENTERPRISE EMPOWERMENT OF MUSTAHIK IN PALU CITY - Uswatun Hasanah; Nurfitriani; Muthmainnah MD (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines the contribution of productive zakat to strengthening the economic resilience of mustahik households in the post-disaster context of Palu City. It addresses the gap between the high potential of zakat and its still limited role in supporting sustainable microenterprise recovery after disaster. A mixed-methods approach was employed by combining survey data from 60 productive zakat beneficiaries of BAZNAS Kota Palu during 2019–2024, in-depth interviews, focus group discussions, and document analysis. Quantitative data were analyzed using descriptive statistics, validity and reliability tests, and simple linear regression. Qualitative data were examined through thematic analysis. The findings indicate a positive and significant relationship between productive zakat and household economic resilience. The regression coefficient was 0.474 (β = 0.773, t = 9.271, p < 0.001), while the model accounted for 59.7% of the observed variation in household economic resilience within the beneficiary sample. Qualitative findings show that productive zakat supported mustahik in increasing business capital, purchasing production tools, restarting disrupted businesses, expanding trading activities, and fulfilling basic household needs. This study is limited to productive zakat beneficiaries and does not include a non-beneficiary comparison group. Therefore, the findings should be interpreted as evidence of a significant relationship rather than definitive causal proof. Future studies should use comparison groups and longitudinal data to examine causal and long-term effects more rigorously. This study contributes to Islamic philanthropy and post-disaster recovery studies by integrating maqāṣid al-sharī‘ah and social capital theory to understand productive zakat as a household resilience and microenterprise empowerment instrument in Palu City.